Intrusion detection systems - Di Pietro, Roberto; Mancini, Luigi V. (Advances in information security, 2008)
This carefully written book is an edited volume by world class leaders within computer network and information security presented in an easy-to-follow style. It introduces defense alert systems against computer and network attacks, and covers much more